2019
DOI: 10.1371/journal.pone.0217842
|View full text |Cite
|
Sign up to set email alerts
|

MagA expression attenuates iron export activity in undifferentiated multipotent P19 cells

Abstract: Magnetic resonance imaging (MRI) is a non-invasive imaging modality used in longitudinal cell tracking. Previous studies suggest that MagA, a putative iron transport protein from magnetotactic bacteria, is a useful gene-based magnetic resonance contrast agent. Hemagglutinin-tagged MagA was stably expressed in undifferentiated embryonic mouse teratocarcinoma, multipotent P19 cells to provide a suitable model for tracking these cells during differentiation. Western blot and immunocytochemistry confirmed the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…As shown in Fig. 5a, R 2 * increased after iron supplementation compared to untreated cultures (−Fe vs +Fe, p < 0.001), consistent with the avid iron import activity in P19 cells reported in a previous study 15 . Upon removal of extracellular iron supplementation, R 2 * decreased to baseline levels within 4 hours (+Fe vs 4h-Fe, p < 0.001), consistent with reported iron export activity in P19 www.nature.com/scientificreports www.nature.com/scientificreports/ cells 15 and clarifying the time course of iron export.…”
Section: Mri Relaxation Rates To Examine Possible Changes In Mr Relasupporting
confidence: 91%
See 3 more Smart Citations
“…As shown in Fig. 5a, R 2 * increased after iron supplementation compared to untreated cultures (−Fe vs +Fe, p < 0.001), consistent with the avid iron import activity in P19 cells reported in a previous study 15 . Upon removal of extracellular iron supplementation, R 2 * decreased to baseline levels within 4 hours (+Fe vs 4h-Fe, p < 0.001), consistent with reported iron export activity in P19 www.nature.com/scientificreports www.nature.com/scientificreports/ cells 15 and clarifying the time course of iron export.…”
Section: Mri Relaxation Rates To Examine Possible Changes In Mr Relasupporting
confidence: 91%
“…Iron particles shorten T 1 and T 2 , resulting in a signal increase in T 1 -weighted images (positive contrast) while producing a signal loss in T 2 -weighted images (negative contrast). While Liu et al 15 showed no influence of changes in extracellular iron on T 1 -weighted images in P19 cell phantoms, if hepcidin activity alters the LIP as proposed above, that might also influence T 1 since it depends on the energy transfer between spins and the surrounding lattice. Thus, if chemical form of surrounding atoms or their compartmentalization is altered under different conditions of iron supplementation and hepcidin-mediated regulation of iron export, this might influence the efficiency of energy transfer and therefore, T 1 .…”
Section: Intracellular Iron Analysis Iron Uptake By Mammalian Cells mentioning
confidence: 87%
See 2 more Smart Citations
“…al. [ 171 ] extended the efficacy of MTB magA gene when transfected into the genome of mouse multipotent P19 cells to promote the intracellular production of magnetite NPs as an efficient MRI contrast agent.…”
Section: In Vivo Biosynthesis Of Inorganic Nanomaterials Using Mammentioning
confidence: 99%